Analisis Pemasaran Industri Batik Tulis Dalam Upaya Peningkatan Pendapatan Tenaga Kerja Di Kecamatan Danau Teluk Kota Jambi - Putri Wahyuni; Rafidah Rafidah; M. Maulana Hamzah (Universitas Sains dan Teknologi Komputer, 2024)
The results of the research show that the marketing of the batik industry is an effort to increase labor income in Danau Teluk District, Jambi City by looking at market needs, current trend needs both among students and also among workers so that consumers who come must be met according to their needs. Obstacles in increasing the income of batik workers in Danau Teluk District, Jambi City are caused by employee negligence in working because they do not comply with the instructions given, income according to work ability and difficulties in marketing.